2021
DOI: 10.1002/ccr3.5107
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypothyroidism‐induced rhabdomyolysis: A case report

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
(18 reference statements)
2
12
0
Order By: Relevance
“…The patient was also treated with intravenous fluids and levothyroxine treatment. 3 Similar to our report, this patient had no precipitating factors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The patient was also treated with intravenous fluids and levothyroxine treatment. 3 Similar to our report, this patient had no precipitating factors.…”
Section: Discussionsupporting
confidence: 88%
“… 2 Clinical features of rhabdomyolysis range from mild increases in creatinine kinase (CK) to medical emergencies like disseminated intravascular coagulation (DIC), acute renal failure, and cardiac arrhythmias. 3 Although hypothyroidism-related rhabdomyolysis can be encountered in clinical practice, it is a very unusual combination. 4 It has been known that hypothyroidism is associated with some degree of myalgia and muscle stiffness, but it can also be a cause of life-threatening rhabdomyolysis with end-organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…The intake of these foods in large amounts can cause or aggravate thyroid dysfunction, but most of these goiter-causing chemicals are inactivated when foods are cooked [37]. Although these patients have many predisposing factors, some case reports indicate that the occurrence of RM may not be related to obvious predisposing factors [4,38,40,41]. Therefore, an RM diagnosis cannot be based on whether a predisposing factor is identified in clinical practice.…”
Section: Rm Caused By Hypothyroidismmentioning
confidence: 99%
“…Most patients have RM in the context of a history of hypothyroidism, but in rare cases, no history of thyroid disease is reported. If RM is the first symptom, the likely outcome is a missed diagnosis or misdiagnosis [38,41]. Salehi et al summarized 10 previously reported cases of RM caused by hypothyroidism in adults.…”
Section: Rm Caused By Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation